Korelasi Antara Adversity Quotient Dengan Selfefficacy Pada Siswa Kelas XII SMA Negeri Di Kota Banda Aceh - Iin Salwa Kamalia; Abu Bakar; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2019)
Adversity quotient and self-efficacy are needed by individuals to be able to optimize themselves and are two factors that influence student success. This study aims to determine the conditions and the relationship between adversity quotient with self-efficacy in class XII students of SMA Negeri in Banda Aceh. The study uses a quantitative approach with descriptive and correlation methods. The study population was all students of class XII in 6 public high schools in the city of Banda Aceh. The sampling method is done using multistage random sampling which was to randomize school samples and use the Slovin formula to determine the number of student samples. The schools that became the sample of the research were Banda Aceh 5 SMA, Banda Aceh 6 SMA and Banda Aceh 12 SMA and the number of samples that were used as research respondents were 222 students. The hypothesis examined in this study was there is a relationship between adversity quotient and self-efficacy. Data collection tools used are the adversity quotient scale and self-efficacy scale in the form of a Likert scale. The results showed that the adversity quotient of dominant students was in the medium category and the level of self-efficacy of the students was also dominant in the medium category. The results also showed a significant positive relationship between adversity quotient and self-efficacy with coefficients r = 0.666 and p = 0,000. This means that the higher the adversity quotient, the higher the student's self-efficacy. Vice versa, if the adversity quotient is low then the student's self-efficacy will also be low.Keywords: Adversity Quotient, Self-Efficacy, High School Student ABSTRAK Adversity quotient dan self-efficacy sangat diperlukan oleh individu untuk dapat mengoptimalkan diri dan merupakan dua faktor yang mempengaruhi keberhasilan siswa. Penelitian ini bertujuan untuk mengetahui kondisi dan hubungan antara adversity quotient dengan self-efficacy pada siswa kelas XII SMA Negeri Di Kota Banda Aceh. Penelitian menggunakan pendekatan kuantitatif dengan metode  deskriptif dan korelasi. Populasi penelitian adalah seluruh siswa kelas XII di 6 SMA Negeri dikota Banda Aceh. Metode pengambilan sampel dilakukan menggunakan multistage random sampling yaitu untuk randominasi sampel sekolah dan menggunakan rumus slovin untuk menentukan jumlah sampel siswa. Sekolah yang menjadi sampel penelitian yaitu SMA Negeri 5 Banda Aceh, SMA Negeri 6 Banda Aceh dan SMA Negeri 12 Banda Aceh dan jumlah sampel yang dijadikan responden penelitian sebanyak 222 siswa. Hipotesis pada penelitian ini adalah adanya hubungan antara adversity quotient dan self-efficacy. Alat pengumpulan data yang digunakan adalah skala adversity quotient dan skala self-efficacy dalam bentuk skala likert. Hasil penelitian menunjukkan adversity quotient siswa dominan berada pada katagori sedang dan tingkat self-efficacy siswa juga dominan berada pada katagori sedang. Hasil penelitian juga menunjukkan adanya hubungan yang signifikan positif antara  adversity quotient dan self-efficacy dengan koefisien r = 0,666 dan p =  0,000. Artinya semakin tinggi adversity quotient maka semakin tinggi  self-efficacy siswa. Begitupun sebaliknya, apabila adversity quotient rendah maka self-efficacy siswa juga ikut rendah.Kata kunci : Adversity Quotient, Self-Efficacy, Siswa SMA